تأثير التغذية الراجعة البايوكينماتيكية في فاعلية إتقان أداء مهارة القلبة الهوائية الخلفية المكورة على بساط الحركات الأرضية - ألبياتي, فردوس مجيد أمين; احمد, عبد الستار محمد علي (Sulaimani Journal for Humanities, 2018)
Featuring game gymnastics performance difficult and serial vehicle and skills, so the researchers have observed that skill front air summersault of important and the basic skills on a table floor movements So it was her education on the faculty of Physical Education and sport Sciences students a its relevance Addition as part of the education methodology for students of the third phase and this with the consequence steps on a teach her instructional are correct and mechanical. The objective is to identify the related the variables a mechanical skill of front air a somersault on the table floor movements, Feedback program positioning on the by some the mechanical variables and tracks the kinetic. And from it conclude that payment and balling phase and landing was a moral indication that the educational curriculum of correcting back mechanical effect on the skill mastered background summersault.